Impact of nanomechanical resonances on lasing from electrically pumped quantum dot micropillars - Czerniuk, T.; Tepper, J.; Akimov, A. V.; Unsleber, S.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Bayer, M. (Applied Physics Letters)
We use a picosecond acoustics technique to modulate the laser output of electrically pumped GaAs/AlAs micropillar lasers with InGaAs quantum dots. The modulation of the emission wavelength takes place on the frequencies of the nanomechanical extensional and breathing (radial) modes of the micropillars. The amplitude of the modulation for various nanomechanical modes is different for every micropillar which is explained by a various elastic contact between the micropillar walls and polymer environment.

Photon-Statistics Excitation Spectroscopy of a Quantum-Dot Micropillar Laser - Kazimierczuk, T.; Schmutzler, J.; Aßmann, M.; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M. (Physical Review Letters)
We introduce photon-statistics excitation spectroscopy and exemplarily apply it to a quantum-dot micropillar laser. Both the intensity and the photon number statistics of the emission from the micropillar show a strong dependence on the photon statistics of the light used for excitation of the sample. The results under coherent and pseudothermal excitation reveal that a description of the laser properties in terms of mean input photon numbers is not sufficient. It is demonstrated that the micropillar acts as a superthermal light source when operated close to its threshold. Possible applications for important spectroscopic techniques are discussed.

Novel mechanisms of optical harmonic generation on excitons in semiconductors - Yakovlev, D. R.; Warkentin, W.; Brunne, D.; Mund, J.; Pavlov, V. V.; Rodina, A. V.; Pisarev, R. V.; Bayer, M. (Nonlinear Optics and Applications IX)

Detection of ultrasonic plate waves using ceramic strip transducers - Claes, Leander; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (Proceedings SENSOR 2015)
Keywords: piezoceramics; strip transducers; plate waveguide; dispersion diagram

Inclusive Beliefs and Self-Efficacy Concerning Inclusive Education Among German Teacher Trainees and Student Teachers - Scheer, David; Scholz, Markus; Rank, Astrid; Donie, Christian (Journal of Cognitive Education and Psychology)

„Alle außer Aaron...“ – Fallbezogene Selbstwirksamkeitserwartungen, Einstellungen und Überzeugungen zukünftiger Lehrkräfte im Kontext Inklusion - Scheer, David; Scholz, Markus; Rank, Astrid; Donie, Christian (Zeitschrift für Heilpädagogik)

Measurement and Analysis of oﬀshore fog occurrences - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 95th AMS Annual Meeting)

Messtechnisches Prinzip eines neuen Einstrahlungsmessgerätes - Bendfeld, Jörg; Balluff, Stefan; Bermpohl, Wolfgang (Wissenschaftliche Verhandlungen 2015 der Deutschen Physikalischen Gesellschaft)

Performance of MERRA Data in Oﬀshore Wind Energy Applications - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Advanced Integration of Oﬀshore Wind Energy into the Grid System by Power to Gas - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Comparison of micro inverters based on practical analysis - Sadati, A.M.; Krauter, Stefan; Bendfeld, Jörg (2015 5th International Youth Conference on Energy (IYCE))

Effective large-scale PV integration: Methods to match load profile with actual PV output - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Assessment of renewable energy resources in cameroon and special regards on energy supply - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Assessment of renewable energy resources and the use of hydro power for fluctuation compensation in Cameroon - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Cost, performance, and yield comparison of eight different micro-inverters - Krauter, Stefan; Bendfeld, Jörg (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

BOS cost reduction via direct PV charging of electrical vehicles - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Stabilizing oﬀshore wind farm power feed-in via power to gas storage systems - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Discovering the potential for oﬀshore windfarms trough measurements - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Wind power forecasting for oﬀshore wind farms - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore wind energy development based on Merra data - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)